Моделювання обсягів замовлень та рівня товарних запасів - Власюк, Ю. О.; Педченко, Анна Павлівна; Педченко, Анна Павловна; Pedchenko, Hanna (My University, 2020)
UK: В статті розглянуто особливості методики ігрового моделювання економічних процесів, а саме: моделювання управління товарними запасами підприємства роздрібної торгівлі. Обґрунтовано доцільність застосування «гри з природою» з метою оптимізації створення товарних запасів молочної продукції для малого підприємства роздрібної торгівлі. Сформовано практичну модель ділової гри з прийняття управлінських рішень. EN: The peculiarities of the game modeling methodology of economic processes application, namely the inventory management of a retail trade enterprise modeling have been considered in the article. It was noted that the format of retail organization is one of the crucial factors that influence the choice of inventory management model. A trading enterprise has been considered in the format of a retail outlet. The emphasis is focus on the need to apply a stock management model with a fixed time interval between orders for the specified trading entity format. The feasibility of using "game with nature" to optimize the dairy commodities formation for a small retailer has been substantiated.When using a game models with a move by nature it is necessary to keep in mind that the player nature is not aim to active counteraction and is indifferent to the controlled process consequences.The practical decision-making model of business game management had been formed. The characteristics of formalized game (game participants, each participant possible strategies, winnings functions, satisfaction degree reflecting of interests, results of the game to which the chosen strategies lead) had been given. In order to evaluate entrepreneur pure strategies, the following criteria had been considered: maximax criterion (extreme optimism), Wald's maximin criterion (extreme pessimism), Savage minimax regret criterion, Bayes-Laplace criterion (maximum average gains), Hurwicz criterion (pessimism and optimism).The optimal amount of inventories for a small retail business, depending on the entrepreneur purpose has been determined.
Simulаtion of orders аnd inventory levels
Keywords: моделювання; теорія ігор; оптимальна стратегія; товарні запаси; modeling; game theory; optimal strategy; inventory